The students' creative thinking ability in elementary schools through RME - Wulandari, Desy; Johar, Rahmah; Bahrun, Bahrun (SAINTIS Publishing, 2023)
One of the abilities that students need to have is the ability to think creatively. This is because with this ability students can solve problems in different ways. This study aims to determine the effectiveness of RME on the results of students' creative thinking abilities in elementary schools. This type of research is experimental research. The research subjects were fourth-grade students at SD Negeri 5 Lhokseumawe. Research data was collected through a creative thinking test. In this study, the researchers observed while the model teacher as a teacher involved 20 students. Data were analyzed descriptively and qualitatively based on the results of students' creative thinking tests. The results of the study concluded that most students' creative thinking abilities were in the very creative category.